Phase-Induced Frequency Conversion and Doppler Effect With Time-Modulated Metasurfaces - Ramaccia, Davide; Sounas, Dimitrios L.; Alu, Andrea; Toscano, Alessandro; Bilotti, Filiberto (IEEE transactions on antennas and propagation, 2020)
Metasurfaces consisting of electrically thin and densely packed planar arrays of subwavelength elements enable an unprecedented control of the impinging electromagnetic fields. Spatially modulated metasurfaces can efficiently tailor the spatial distribution of these fields with great flexibility. Similarly, time-modulated metasurfaces can be successfully used to manipulate the frequency content and time variations in the impinging field. In this article, we present time-modulated reflective metasurfaces that cause a frequency shift to the impinging radiation, thus realizing an artificial Doppler effect in a nonmoving electrically thin structure. Starting from the theoretical analysis, we analytically derive the required time modulation of the surface admittance to achieve this effect and present a realistic time-varying structure, based on a properly designed and dynamically tuned high-impedance surface. It is analytically and numerically demonstrated that the field emerging from the metasurface is up-/down-converted in frequency according to the modulation profile of the metasurface. The proposed metasurface concept, enabling a frequency modulation of the electromagnetic field "on-the-fly," may find application in telecommunication, radar, and sensing scenarios.